Flexibility of Working Hours on Employee Performance Through Work Motivation at PT PLN (Persero) UIP3B Sulawesi - Ari Rudianto; Dian S Parawansa; Nuraeni Kadir (YUME : Journal of Management, 2023)
This research aims to analyze the effect of working hour flexibility on work motivation and employee performance. Analyzing the influence of work motivation on employee performance and the influence of working hour flexibility on employee performance through work motivation. A quantitative approach tests and analyzes factors that influence employee performance. Research location in Sulawesi. The population in this study consisted of employees who worked at PT PLN (Persero) UIP3B Sulawesi, with a total of 1,343 employees. Drawing the number of samples in this study used the Slovin approach with a margin of error of 10 percent. The data collection technique uses a questionnaire. The measurement scale used is a Likert scale with five components. The data analysis technique in this research uses path analysis. The research results show that flexibility in working hours has a positive and significant effect on work motivation and employee performance. The variable working hour flexibility positively and significantly affects employee performance through work motivation. The work motivation variable has a positive and significant effect on employee performance. Kata Kunci: Flexibility of Working Hours; Human Resource Management; Work Motivation; Employee Performance